GRAVY (FRUITS AND EMBERS) - Bayinat Basha Al-Bajali, Abul Firdaus (IJRDO - Journal of Social Science and Humanities Research, 2023)
This research deals with the talk about earning by explaining its linguistic and idiomatic concept, then dealing with the importance and legitimacy of earning in the Qur'an and Sunnah, explaining the number of verses in which there is an item in the Qur'an, and explaining its merits and fruits in this world and the hereafter, such as: blessing, feeling the grace of God Almighty, and a sense of reassurance. Satisfaction and peace of mind, answering supplications, infallibility of punishments, and protection from fireFinally, the research deals with the dangers of the globalization of the culture of profit, because the winds of globalization are still blowing us from every direction, and they are saturated with the obsession of the culture of gain, and infused with the pride of maximizing profit, and fascinated by its intense interest in the idea of ​​expanding the use of machine technology in all aspects of social life. Attention should be paid to the dangers of total immersion in such a type of culture, and to be wary of copying it in our reality without scrutiny. To avoid negative repercussions.